Low-molecular-weight heparin in addition to low-dose aspirin for preventing preeclampsia and its complications: A systematic review and meta-analysis - Zheng, Li; Xia, Binbin; Yuan, Yuan; Wang, Yuran; Wang, Yan (Frontiers in Cardiovascular Medicine, 2022)
Background In this systematic review, we aimed to investigate the efficacy and safety of adding low-molecular-weight heparin (LMWH) or unfractionated heparin to low-dose aspirin (LDA) started ≤16 weeks'gestation in the prevention of preeclampsia (PE) in high-risk women. Methods PubMed, Cochrane Library, Embase, and ClinicalTrials.gov databases were searched from their inception to April 2022 for randomized controlled trials (RCTs) that to determine whether the combined treatment of LMWH and LDA is better than single anticoagulant drugs in preventing PE and improving live birth rate of fetus in high-risk women with pregnancy ≤16 weeks. We also searched Embase, OVID MEDLINE and OVID MEDLINE in-process using the OVID platform. Results 14 RCTs involving 1,966 women were found. The LMWH (or unfractionated heparin) and LDA groups included 1,165 wemen, and the LDA group included 960 women. The meta-analysis showed that the addition of LMWH to LDA reduced the risk of PE (RR: 0.59, 95% CI: 0.44-0.79, P < 0.05), small-for-gestational age (SGA, RR: 0.71, 95% CI: 0.52-0.97, P = 0.03), fetal and neonatal death (RR: 0.45, 95% CI: 0.23-0.88, P = 0.02) and gestational hypertension (RR: 0.47, 95% CI: 0.25-0.90, P = 0.02). It is worth emphasizing that LMWH (or unfractionated heparin) combined with LDA did not increase the risk of bleeding. Conclusions LMWH combined with LDA can effectively improve the pregnancy outcome of women with high risk factors for PE and its complications. Although this study showed that combined medication also did not increase the risk of bleeding, but such results lack the support of large sample size studies. The clinical safety analysis of LMWH combined with LDA in patients with PE should be more carried out.